2009
DOI: 10.1210/jc.2008-2686
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Protein Synthesis and Balance Responsiveness to Essential Amino Acids Ingestion in the Presence of Elevated Plasma Free Fatty Acid Concentrations

Abstract: Elevated plasma FFA concentrations do not interfere with the response of muscle protein synthesis and balance to a bolus ingestion of EAAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 43 publications
2
29
3
Order By: Relevance
“…This is, to our knowledge, the first study to acutely induce anabolic resistance in humans by lipid administration. However, these findings are in contrast to the study of Katsanos et al (22), where lipid was intravenously administered at nearly twice the rate and no blunting of the 50% increase in muscle protein synthesis was observed in response to the ingestion of 7 g essential amino acids. The differences are difficult to reconcile but may be due to the hyperinsulinemic-euglycemic clamp in the current study, which likely impaired fat oxidation and caused an accumulation of intracellular lipid metabolites (23).…”
Section: Discussioncontrasting
confidence: 93%
“…This is, to our knowledge, the first study to acutely induce anabolic resistance in humans by lipid administration. However, these findings are in contrast to the study of Katsanos et al (22), where lipid was intravenously administered at nearly twice the rate and no blunting of the 50% increase in muscle protein synthesis was observed in response to the ingestion of 7 g essential amino acids. The differences are difficult to reconcile but may be due to the hyperinsulinemic-euglycemic clamp in the current study, which likely impaired fat oxidation and caused an accumulation of intracellular lipid metabolites (23).…”
Section: Discussioncontrasting
confidence: 93%
“…The effects of increasing FFA availability on direct (Katsanos et al, 2009;Stephens et al, 2014) or indirect (Ferrannini et al, 1986;Gormsen et al, 2008) measures of MPS have also been studied in humans. Katsanos and colleagues (2009) reported little attenuation of MPS in response to the ingestion of 7 g of EAAs after the initiation of a 10 h intralipid infusion (20% Liposyn, 90 ml h −1 ).…”
Section: Increased Fat Availabilitymentioning
confidence: 99%
“…A decrease in the activity of the insulin signaling cascade as a result of fatty acid load would be expected to attenuate the insulin-induced response to protein synthesis via the downstream protein kinase B (also known as AKt) and target of rapamycin signaling pathway. However, the data of Katsanos et al (1) showed that even in the presence of fatty acid-induced insulin resistance, the protein synthesis response to amino acid load was not impaired. Studies in healthy humans have shown that amino acids stimulate skeletal muscle protein synthesis through an AKt-independent pathway (11,20).…”
mentioning
confidence: 96%
“…By using isotopic tracers in combination with arteriovenous balance measurements across the leg and by quantifying tracer incorporation into muscle proteins, Katsanos et al (1) have presented a detailed analysis of protein kinetics in the skeletal muscle. As anticipated, increase in plasma free fatty acids resulted in the development of insulin resistance (2).…”
mentioning
confidence: 99%